2014
DOI: 10.1007/s10681-014-1294-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide association mapping of agro-morphological and disease resistance traits in sugarcane

Abstract: The objectives of the study were to assess genome wide association study (GWAS) for sugarcane on a panel of 183 accessions and to evaluate the impact of population structure and family relatedness on QTL detection. The panel was genotyped with 3327 AFLP, DArT and SSR markers and phenotyped for 13 traits related to agro-morphology, sugar yield, bagasse content and disease resistances. Marker-trait associations were detected using (i) general linear models that took population structure into account with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 71 publications
7
59
0
1
Order By: Relevance
“…In case of the qualitative traits, it was observed that the MTAs were able to explain a satisfactorily higher proportion of the phenotypic trait variation as compared to that of quantitative traits. Similar finding were also reported in previous MTA studies with sugarcane (Debibakas et al 2014;Guoy et al 2015;Banerjee et al 2015). This could be due to the fact that the qualitativephenotypic traits were not quantitatively governed and hence had a reduced possibility of missing out rare variants thereby minimizing the chances of missing heritability.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In case of the qualitative traits, it was observed that the MTAs were able to explain a satisfactorily higher proportion of the phenotypic trait variation as compared to that of quantitative traits. Similar finding were also reported in previous MTA studies with sugarcane (Debibakas et al 2014;Guoy et al 2015;Banerjee et al 2015). This could be due to the fact that the qualitativephenotypic traits were not quantitatively governed and hence had a reduced possibility of missing out rare variants thereby minimizing the chances of missing heritability.…”
Section: Discussionsupporting
confidence: 88%
“…Out of all the qualitative traits, the maximum six markers were identified for leaf curvature, while a single MTA was identified for few descriptors like bud cushion, bud size, growth crack, pithiness, and shape of bud (Table 5). On individual basis, a significant proportion of trait variation ranging from 16% (marker IISR_9_150 for colour of dewlap) to 40% (marker IISR_227_150 for root band width) was explained by the markers which is comparatively higher than the traits variation explained in previously reported marker-trait association studies with sugarcane (Debibakas et al 2014;Guoy et al 2015;Banerjee et al 2015). No MTA was detected for internode colour (unexposed).…”
Section: Marker-trait Associationsmentioning
confidence: 63%
See 2 more Smart Citations
“…Bundock et al (2012) conducted the solution-based hybridization (Agilent SureSelect) to capture the exome regions of sugarcane using sorghum and sugarcane coding probes, enriched the genome 10-11 fold, and detected 270,000-280,000 SNPs in each genotype of the material tested. At the moment, a great number of SNPs from a genome or haplotype can be generated by using high capacity genome sequencing instruments or high density oligonucleotide arrays (Zhu et al, 2008 Huang et al, 2010); resistance to sugarcane yellow leaf virus using 3,949 polymorphic markers (DArT and AFLP) on 189 genotypes (Debibakas et al, 2014); agro-morphological traits, sugar yield disease resistance and bagasse content using 3,327 DArT, AFLP and SSR markers on 183 genotypes (Gouy et al, 2015); and sucrose and yield contributing traits using 989 SSR markers on 108 genotypes (Banerjee et al, 2015). Employing the Affymetrix GeneChip Sugarcane Genome Array, Casu et al (2007) identified 119 transcripts associated with enzymes of cell-wall metabolism and development on sugarcane variety Q177.…”
Section: Whole Genome and Transcriptome Sequencing Approachesmentioning
confidence: 99%